PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT IBU HAMIL DI WILAYAH KERJA PUSKESMAS KOPELMA DARUSSALAM BANDA ACEH - Dewi Saputri; Afrina Afrina; Ridha Kurnia Shalina (Journal of Syiah Kuala Dentistry Society, 2016)
Pregnancy is a special stage in women life which caused the alteration in human body including the oral cavity. These alteration occur as a result of increased secretion of hormones estrogen and progesterone. The increased secretion of this hormone, makes pregnant woman exposed to problems with oral health. The behavior of oral health maintenance can reduce problems at oral cavity of pregnant woman. The behavior of oral health maintenance consisting of knowledge, attitudes and practice. The purpose of this study is to description the behavior of oral health maintenance in pregnant woman at community health centre in Kopelma Darussalam, Banda Aceh. This study was a descriptive survey used questionnaire with 60 people as research subject. The result showed that pregnant woman who have good behavior in oral health maintenance is 25%, moderate behavior is 55% and bad behavior is 20%. It can concluded that pregnant woman in the work area of community health centre Kopelma Darussalam had moderate behavior in maintenance of oral health.Keywords: Pregnancy Woman, Behavior, Oral Health Maintenance